2019
DOI: 10.33793/acperpro.02.03.108
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Effect of Soil Moisture on Thermal Performance of Earth Air Heat Exchanger

Abstract: ÖzetToprak Hava Isı Değiştirici (THID) sistemleri toprağın sahip olduğu yüksek enerji potansiyelinin kullanımına dayalı yenilenebilir enerji sistemleridir. Basit bir yapısı olmasına karşın ısıl performansına etki eden birden çok parametre bulunmaktadır. Toprak altına gömülü boru sistemi ve bir fandan meydana gelen THID'in kurulumunda bu parametrelerin göz önünde bulundurulması gerekmektedir. Bu çalışmada, THID'in yerleştirildiği toprağın bir sulama hattı yerleştirilerek nemlendirilmesinin ısıl performansa etki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The effect of humidification of soil was studied on them. It has been found that moist soil improves performance for both materials by almost 10% (Demirtas¸ and Bulut, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of humidification of soil was studied on them. It has been found that moist soil improves performance for both materials by almost 10% (Demirtas¸ and Bulut, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Positive (Demirtas¸ and Bulut, 2019) Increase in moisture of soil by 7% decreases the output temperature by 1.6 o C in summer season.…”
Section: Findings About Effect Of Climate On the Performance Of Eahe ...mentioning
confidence: 99%